2021
DOI: 10.1002/ijgo.14015
|View full text |Cite
|
Sign up to set email alerts
|

Consequences and implications of the coronavirus disease (COVID‐19) on pregnancy and newborns: A comprehensive systematic review and meta‐analysis

Abstract: Background Pregnant patients are potentially vulnerable to COVID‐19. Objectives To clarify the clinical features of COVID‐19 and analyze maternal/fetal morbidity and mortality and the obstetric and neonatal outcomes of pregnant patients. Search strategy Embase, PubMed, Web of Science, CINAHAL, LILACS, Google Scholar, and Scopus. Selection criteria Articles published from December 2019 to February 2021. Data collection and analysis The reviewers extracted relevant data from the full‐text. Data synthesis was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 40 publications
2
23
1
6
Order By: Relevance
“…The phenomenon of lower preterm birth and cesarean section in pregnant women with COVID-19 require careful assessment. Several studies have reported a higher rate of preterm birth and cesarean section in pregnant women with COVID-19; however, some results are contradictory [12][13][14][15][16][17][18][19]. In addition, the most frequent causes of early emergency cesarean sections were reported to be fetal distress and worsening respiratory symptoms in pregnant women with COVID-19 [19].…”
Section: Study Contributionmentioning
confidence: 99%
“…The phenomenon of lower preterm birth and cesarean section in pregnant women with COVID-19 require careful assessment. Several studies have reported a higher rate of preterm birth and cesarean section in pregnant women with COVID-19; however, some results are contradictory [12][13][14][15][16][17][18][19]. In addition, the most frequent causes of early emergency cesarean sections were reported to be fetal distress and worsening respiratory symptoms in pregnant women with COVID-19 [19].…”
Section: Study Contributionmentioning
confidence: 99%
“…The study comprised 10,047 expectant mothers with COVID-19, out of which 71.6% were in their 3 rd trimester. Pregnant patients' placenta, breast milk, navel string, and amniotic fluid did not indicate COVID-19 [82] .…”
Section: Latest Studiesmentioning
confidence: 85%
“…En nuestro medio 18 y en otros países 19 se ha criticado la falta de datos desagregados por sexo/género sobre indicadores clínicos y epidemiológicos de la COVID-19. Respecto a la salud reproductiva, se ha resumido la evidencia sobre el efecto de la COVID-19 en el acceso a servicios de aborto, anticonceptivos y pruebas del virus de la inmunodeficiencia humana, además de cambios en los comportamientos sexuales, menstruación e intenciones de embarazo 20 , y efectos durante el embarazo 21 , procesos perinatales 22 y violencia machista 23 .…”
Section: Resultados Y Discusiónunclassified